Alternative South–South development collaboration? The role of China in the Coega Special Economic Zone in South Africa. (4th December 2019) - Thompson, Lisa
Summary: Aid, in the form of financial aid and investment, has become increasingly prevalent in both bilateral and multilateral partnerships in the BRICS. In Africa, the Forum on China–Africa Cooperation provides the official framings for forms of development assistance to the continent, with financial forms of aid available through the New Development Bank and the China–Africa Development Bank (CADFund). This article explores how Chinese international development assistance has influenced South Africa's economic growth and development strategies and is reshaping South Africa as "gateway" to Africa and continental leader. Special economic zones (SEZs) have become a prioritised form of BRICS development collaboration particularly in terms of Chinese trade and investment expansionism into Africa through South Africa. Chinese international development assistance and foreign direct investment in South Africa in particular are very notable and have been strengthened during the Chinese official state visit prior to the Johannesburg BRICS Summit in 2018. The article critically analyses the development policy discourse on BRICS spearheading an alternative model of South–South international cooperation by examining the Coega SEZ in South Africa, hailed as the most SEZ in Africa. The article critically examines the development alternative potential of the Coega SEZ.